2003
DOI: 10.1176/appi.ajp.160.5.835
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Stimulation in the Treatment of Depression

Abstract: Objective: Transcranial magnetic stimulation (TMS) is a noninvasive and easily tolerated method of altering cortical physiology. The authors evaluate evidence from the last decade supporting a possible role for TMS in the treatment of depression and explore clinical and technical considerations that might bear on treatment success. Method:The authors review English-language controlled studies of nonconvulsive TMS therapy for depression that appeared in the MEDLINE database through early 2002, as well as one st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
250
0
28

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 452 publications
(284 citation statements)
references
References 60 publications
6
250
0
28
Order By: Relevance
“…In depressed patients, a recent meta-analysis (Gershon et al, 2003) revealed that the most efficacious rTMS treatment protocols applied highfrequency (ie 5-20 Hz) rTMS over the left MDLFC for 5-20 days, resulting in improvement in depression ratings in 41% of the patients studied (n ¼ 139). In healthy subjects, however, the short-term changes in affect observed following a single rTMS session are often opposite to the changes in mood observed in depressed patients, namely more negative affect following 10-Hz rTMS applied over the left MDLFC (eg George et al, 1996;Pascual-Leone et al, 1996;Martin et al, 1997; but for negative findings, see Mosimann et al, 2000;Padberg et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In depressed patients, a recent meta-analysis (Gershon et al, 2003) revealed that the most efficacious rTMS treatment protocols applied highfrequency (ie 5-20 Hz) rTMS over the left MDLFC for 5-20 days, resulting in improvement in depression ratings in 41% of the patients studied (n ¼ 139). In healthy subjects, however, the short-term changes in affect observed following a single rTMS session are often opposite to the changes in mood observed in depressed patients, namely more negative affect following 10-Hz rTMS applied over the left MDLFC (eg George et al, 1996;Pascual-Leone et al, 1996;Martin et al, 1997; but for negative findings, see Mosimann et al, 2000;Padberg et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Quando este dispositivo é posicionado próximo à cabeça de um ser humano, o campo magnético penetra o cérebro e induz um campo elétrico na região adjacente do córtex cerebral. Um campo elétrico de intensidade suficiente despolariza os neurônios corticais, gerando um potencial de ação (Gershon et al, 2003).…”
Section: Estimulação Magnética Transcranianaunclassified
“…Os parâmetros técnicos para a aplicação da EMT no TDM ainda não estão definidos. Não se sabe ainda qual o local exato, número de dias, frequência e intensidade da estimulação (Gershon et al, 2003). Da mesma forma, ainda não se sabe qual população clínica melhor se beneficiaria desta abordagem, não sabendose ainda se seria melhor aplicável à depressão unipolar, bipolar ou psicótica (Gershon et al, 2003).…”
Section: Estimulação Magnética Transcraniana No Tdmunclassified
See 2 more Smart Citations